Pola Orang Tua Mendidik Anak di Desa Sungai Punggu Baru Kecamatan Anjir Muara Kabupaten Barito Kuala - H.M. Hendra (Jurnal Pendidikan Kewarganegaraan, 2015)
This study examines how parents apply the pattern of educating their children in the village of Sungai Punggu Baru Kecamatan Anjir Muara Kabupaten Barito Kuala. In the application studied is how the pattern of educating children, attention and affection of parents to their children, and the parent's responsibility to educate their children. Parents as primary educators in the family, efforts to form the children's personality, and how parents become a good personality educators to educate children through pattern of parents education as well as examples of exemplary parents.The method used in this study is a qualitative method. The technique used is purposive sampling technique. Data was collected through observation (observation), interviews, documentation, and literature study. Source data was taken from interviews with key informants and appropriate documentation of research objects and analyzed by means of data reduction, data display, and conclusion. The data can also be tested on their validity by way of extension of observation, increase persistence, triangulation, and using reference materials.The results showed that the application of the family educating in children is not maximally done by the parents. The low parental education, family economic level of difficulty and lack of knowledge of how to educate children are a fundamental factor in the formation of personality of their children. While the children, something that can affect them are motivation, self-awareness, as well as experience. Errors in educating and exemplary pattern is also one of the causes of the children's personality do not develop properly, educate permissive pattern adopted is not appropriate for the children's development and character formation.Based on the results of this study suggested that parents should be able to guide, educate and support children to get better education, instilling noble values in shaping his personality both internally is through motivation that embedded values of goodness in him, and to improve the supervision of children relationships within the school and community. Changing patterns in permissive educate children with educating democratic pattern so that children are always open with their parents, so existed a close relationship and good communication between children and parents.Keywords : Education, Family, Affection, and Responsibility